COMPUTER TECHNOLOGIES ON SERVE TO TEXTURE ANALYSIS FOR A PERFORMER (Mūzikas akadēmijas raksti, 2024)
The article deals with the author’s concept of a search in figurative writing on the basis of which a method of handling computer technologies for the analysis of setting is being introduced. Examples from clavier and piano pieces by William Byrd, Domenico Scarlatti, Johann Sebastian Bach, Wolfgang Amadeus Mozart and Arnold Schönberg are chosen to demonstrate peculiarities in analysis of compound textures (of combinatorial type). The method of marking figures (patterns) in a texture area with graphic frames helps to explain general and individual mechanisms of creating musical texture.